Tax Incentives and International Capital Flows : The Case of the United States and Japan. (IMF Working Papers; Working Paper, 1989)
This paper explores how the tax treatment of investment and savings affects international capital flows as well as national and global welfare. Focusing on portfolio investment, it evaluates the international effects of capital income taxes in the United States and Japan. During the 1980s, these taxes encouraged capital flows to the United States both by favoring investment in that country and by harming the country's relative savings performance. The paper concludes that the internationalization of financial markets calls for a careful study of the international implications of domestic tax policies.